THE PHENOMENON OF CONSUMER FLEXING OF BRANDED PRODUCTS FOR MEMBERS OF LEGISLATIVE ON SOCIAL MEDIA - sabet al banani; Rini Fidiyani (Universitas Negeri Semarang, 2026)
The practice of flaunting a luxurious lifestyle among public officials through social media has drawn widespread attention, indicating a shift in political communication and self-representation patterns that have the potential to influence public trust and shape a consumerist culture in society. This phenomenon is problematic because it not only touches on social and ethical dimensions but can also lead to legal consequences related to the principles of propriety, integrity, and responsibility through the position obtained. This research has an urgency to legal studies that have not been optimally comprehensive and requires a special study regarding the relationship between officials' flexing with legal principles, government ethics, and social norms in the digital era. This study uses a qualitative method with a normative juridical approach and is supported by non-doctrinal studies through social concept analysis, with data collection techniques in the form of library studies of laws and regulations, legal doctrine, and relevant literature. The results of the study indicate that the flexing phenomenon is influenced by the theory of symbolic consumption and social dramaturgy in the form of the use of modern lifestyles as a means of image formation and status legitimacy. The originality of this research lies in the link between consumer flexing behavior and the legal ethics of public officials in the digital age. This study concludes that there is a need to strengthen ethical regulations and social media oversight mechanisms for legislators.